1995
DOI: 10.1103/physrevlett.74.738
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Submillimeter Electromagnetic Waves by Coherent Phonons

Abstract: We report on the first observation of the emission of electromagnetic radiation from coherent lattice vibrations in a semiconductor. Coherent optical phonons are excited by ultrashort laser pulses in singlecrystal tellurium. THz frequency radiation emitted by the Dember-field-driven phonons is detected by time-resolved THz-emission spectroscopy. The measurements are complemented by optical pump-probe experiments with a polarization-sensitive detection scheme utilizing the symmetry of the Raman tensor. 42.65.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
114
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(123 citation statements)
references
References 11 publications
7
114
2
Order By: Relevance
“…The waves could be detected by the technique of time-resolved THz-emission spectroscopy, in the way similar to used in other radiating superlattice devices [46,47]. Moreover, the spectral signatures of the electron velocity unravel the potential of the acoustically pumped superlattices for an amplification of high-frequency electromagnetic signals involving mechanisms similar to the stable Bloch gain [15,48].…”
Section: Discussionmentioning
confidence: 99%
“…The waves could be detected by the technique of time-resolved THz-emission spectroscopy, in the way similar to used in other radiating superlattice devices [46,47]. Moreover, the spectral signatures of the electron velocity unravel the potential of the acoustically pumped superlattices for an amplification of high-frequency electromagnetic signals involving mechanisms similar to the stable Bloch gain [15,48].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the observation of THz electromagnetic emission from Bloch oscillations [7] and coherent phonons [26], we expect that the SL biased into the Bloch-phonon resonance is a strong emitter of electromagnetic radiation at the LO phonon frequency. Because of the longer dephasing time of the lattice mode, room temperature emission can be obtained for times exceeding the lifetime of pure electronic Bloch oscillations by an order of magnitude [27].…”
mentioning
confidence: 99%
“…For absorbing substances, a unique process has so far not been identified [1]. The experimental evidence indicates that Raman selection rules are strictly obeyed (see, e.g., [3,5,7,13]). However, the oscillation phase varies from material to material, and relative intensities gained from time-domain measurements and spontaneous Raman scattering (RS) do not appear to correlate [4].…”
mentioning
confidence: 99%
“…Following recent advances in femtosecond laser technology, several groups demonstrated that the propagation of light pulses in solids is accompanied by intense lattice vibrations showing a high degree of spatial and temporal coherence [1][2][3][4][5][6][7][8][9]. The availability of coherent phonons at THz frequencies has led to a variety of suggestions for applications and experiments involving, in particular, time-domain spectroscopy of phonons using pumpprobe methods [1][2][3][4][5][6][7][8][9], conversion of mechanical into coherent electromagnetic energy [7], and intriguing proposals relying on photon control of the ionic motion [10,11].…”
mentioning
confidence: 99%
See 1 more Smart Citation